ANALISIS KUALITAS TANAH PADA BEBERAPA TIPE PENGGUNAAN LAHAN DI KECAMATAN NGGAHA ORI ANGGU KABUPATEN SUMBA TIMUR - Aldi Babu Tara Parengu; Yonce Melyanus Killa; Melicorianda Hubi Ndapamuri (Fakultas Pertanian, Program Studi Agroteknologi, 2026)
Soil quality is an important indicator in supporting agricultural productivity and sustainable land management. This study aims to analyze soil quality in several types of land use in Nggaha Ori Angu District, East Sumba Regency. The study was conducted using a survey method with a quantitative descriptive approach at 16 sample points representing the use of rice fields, gardens, fields, shrubs, and savannahs. The parameters analyzed included soil permeability, bulk density, soil texture, soil depth, cation exchange capacity (CEC), organic C, soil pH, and total soil respiration. The results of the study in Nggaha Ori Angu District showed that the soil permeability value ranged from 4.31-17.35 cm/hour with a soil bulk density value between 0.96-1.16 g/cm3. The soil texture was dominated by clay criteria, then silt, and sandy loam with soil depths varying from 10 cm to >50 cm. The pH ranged from 7.17 to 7.95, with a soil CEC of 1.74 to 24.34 cmol(+)/kg and soil organic carbon of 1.56 to 3.00%. Total soil respiration was 0.04–0.84 mg C-CO₂g/day. The Soil Quality Index (SIC) scores ranged from 2.75 to 3.25, categorized as moderate to slightly high. The highest SIC value was found in plantation land use at 3.09, categorized as moderate, while the lowest SIC value was found in shrubland land use at 2.83, categorized as moderate. The average SIC value in Nggaha Ori Angu District was 2.97, categorized as moderate.